2021
DOI: 10.3390/jcm10153197
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Effect Hypothesis of Abused Drugs in a Rat Model of Chronic Morphine Administration

Abstract: A growing body of studies has recently shown that abused drugs could simultaneously induce the paradoxical effect in reward and aversion to influence drug addiction. However, whether morphine induces reward and aversion, and which neural substrates are involved in morphine’s reward and aversion remains unclear. The present study first examined which doses of morphine can simultaneously produce reward in conditioned place preference (CPP) and aversion in conditioned taste aversion (CTA) in rats. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The study also clarified whether MAMPH administered to the PrL affected CTA, neural activity, or plasticity in the mPFC, NAc, amygdala, and hippocampus. Our study found that the short-term administration of MAMPH serves as a cognitive enhancer in a typical animal model of CTA (Yu et al, 2021); however, the model used in this study was not a typical animal model of AD. Repeating these tests in a suitable animal model of AD [e.g., a transgenic (Weishaupt et al, 2018) or a neurotoxic lesion-induced mouse model (Ando et al, 2002) of AD] and examining the effects on CTA under AD conditions remains necessary in future studies to determine whether these findings are applicable in the AD brain.…”
Section: Experimental Limitations and Emerged Issuesmentioning
confidence: 62%
“…The study also clarified whether MAMPH administered to the PrL affected CTA, neural activity, or plasticity in the mPFC, NAc, amygdala, and hippocampus. Our study found that the short-term administration of MAMPH serves as a cognitive enhancer in a typical animal model of CTA (Yu et al, 2021); however, the model used in this study was not a typical animal model of AD. Repeating these tests in a suitable animal model of AD [e.g., a transgenic (Weishaupt et al, 2018) or a neurotoxic lesion-induced mouse model (Ando et al, 2002) of AD] and examining the effects on CTA under AD conditions remains necessary in future studies to determine whether these findings are applicable in the AD brain.…”
Section: Experimental Limitations and Emerged Issuesmentioning
confidence: 62%
“…Under these conditions, amphetamine induced significant taste aversions and place preferences, again demonstrating both aversive and rewarding effects of the same drug and under identical parametric conditions. Subsequent to the initial work by Reicher and Holman, a variety of drugs have now been shown to support both effects in the combined CTA/CPP procedure including 3,4-methylenedioxypyrovalerone (MDPV) [ 144 ], α -pyrrolidinopentiophenone ( α -PVP) [ 104 , 145 , 146 ], nicotine [ 147 ], amphetamine [ 148 150 ], morphine [ 150 157 ], cocaine [ 158 160 ], alcohol [ 161 ], and caffeine [ 162 ]; for several drugs, e.g., ethanol [ 163 ] and ∆ 9 -tetrahydrocannabinol (THC) ([ 164 , 165 ], both taste and place aversions were reported with the combined design (for reviews, see [ 166 , 167 ]).…”
Section: Combined Taste Aversion/place Preference Proceduresmentioning
confidence: 99%
“…Further, adolescents were more sensitive to the rewarding effects of nicotine (and less sensitive to its aversive effects) relative to adults (for comparison, see [ 168 ] who reported these same relative sensitivities of CPP and CTA when separately assessed). Other comparisons across studies have shown that place preference conditioning is comparable when assessed in a combined CTA/CPP design or as an independent CPP and that manipulations in either design impact place preference conditioning similarly (see [ 152 , 157 ] for assessments of the combined CTA/CPP assay with morphine compared to [ 169 , 170 ] for assessments of morphine using only CPP; for a similar comparison with MDPV, see [ 171 ] compared to [ 172 ]; for α -PVP, see [ 104 ] compared to [ 173 , 174 ]; and for caffeine, see [ 162 ] compared to [ 175 ]).…”
Section: Combined Taste Aversion/place Preference Proceduresmentioning
confidence: 99%
See 2 more Smart Citations